The Weissella and Periweissella genera: up-to-date taxonomy, ecology, safety, biotechnological, and probiotic potential - Fusco, Vincenzina; Chieffi, Daniele; Fanelli, Francesca; Montemurro, Marco; Rizzello, Carlo Giuseppe; Franz, Charles M. A. P. (Frontiers in Microbiology, 2023)
Bacteria belonging to the genera Weissella and Periweissella are lactic acid bacteria, which emerged in the last decades for their probiotic and biotechnological potential. In 2015, an article reviewing the scientific literature till that date on the taxonomy, ecology, and biotechnological potential of the Weissella genus was published. Since then, the number of studies on this genus has increased enormously, several novel species have been discovered, the taxonomy of the genus underwent changes and new insights into the safety, and biotechnological and probiotic potential of weissellas and periweissellas could be gained. Here, we provide an updated overview (from 2015 until today) of the taxonomy, ecology, safety, biotechnological, and probiotic potential of these lactic acid bacteria.